Meronymy in Indonesian and Acehnese: A Lexical-Semantic Analysis of Foot-Part Terminology - Desri Wiana; Rusyda Nazhirah Yunus (Journal of General Education and Humanities, 2026)
Semantic typology in lexical systems reveals how languages categorise reality through patterned semantic relations, with meronymy (part–whole structuring) providing a productive domain for examining bodily terminology. This study investigates divergences in the meronymic encoding of kaki ‘leg/foot’ in Indonesian and Acehnese—two geographically proximate and genealogically related Austronesian languages—by examining the processes shaping meronymized lexis, formulating principles of meronymic relatedness, and identifying distinguishing features of the Acehnese partonym kaki. Using a descriptive qualitative design, the study analyses 32 Indonesian and 25 Acehnese foot-related meronyms drawn from KBBI and regional dictionaries, applying an inductive semantic-componential procedure to map hierarchical part–whole configurations. Results show that both languages display well-formed branching meronymic hierarchies but do not converge on a single unified model of the human leg. Indonesian exhibits a more fine-grained hierarchy (e.g., betis ‘calf’, telapak kaki ‘sole’, tumit ‘heel’, punggung kaki ‘instep’), whereas several of these—especially ‘instep’ and ‘calf’—lack fully lexicalised equivalents in Acehnese and are instead expressed through broader or descriptive forms. These differences align with functional salience and perceptual prominence, whereby experientially significant parts receive denser lexical encoding. The study concludes that Indonesians and Acehnese share universal principles of meronymic organisation yet differ markedly in semantic granularity, reflecting cultural perceptions of bodily segmentation. The findings support typological models of partonomy and underscore the need to expand Acehnese lexicographic documentation with native-speaker validation and future analyses across other body regions, including computational corpus-based extraction of meronymic structures.